Effects of polysaccharides autoclave extracted from Flammulina velutipes mycelium on freeze-thaw stability of surimi gels. (1st November 2022) - Qin, Lujie; Fu, Yin; Yang, Fan; Chang, Zhongyi; Zou, Chunjing; Gao, Hongliang; Jiang, Deming; Jia, Caifeng
Abstract: Quality deterioration caused by ice formation and growth is a prevailing problem in frozen food, therefore, exploration of natural cryoprotectants has been attracting more attention. In this study, Flammulina velutipes mycelium polysaccharides (FVP) were obtained by autoclave extraction and their effect on freeze-thaw stability of surimi gels were investigated. The results showed that FVP consisted mainly (59.02%) of high-molecular-weight polysaccharides (>450 kDa), and were composed of Glu, Xyl, Man, Gal, and Fuc in a molar ratio of 33.4: 28.72: 26.31: 8.01: 3.55. FVP (1.0 mg/mL) showed superior Ice Recrystallization Inhibition (IRI) activity. Freeze-thaw stability tests demonstrated that frozen-thawed surimi gels with FVP addition exhibited a more uniform and continuous matrices than the control ones. FVP could significantly improve the water holding capacity, the hardness, springiness and cohesiveness of surimi gels during the repeated freeze-thaw cycles. Studies on water state and properties showed that FVP could decrease the freezable water content, restrict water mobility, and inhibit water migration in frozen surimi gels. These results suggest the potential of FVP as a promising cryoprotectant candidate in the frozen food industry. Graphical abstract: Image 1 Highlights: Flammulina velutipes polysaccharides (FVP) extracted in autoclave showed IRI activity. 0.1% FVP preserved the quality of surimi gels during freeze-thaw cycles. FVP decreased freezable water content, water mobility and migration of surimi gels.